Battery monomer, preparation method thereof and lithium ion battery
By optimizing the electrode structure of the lithium-ion battery and controlling the particle size and density, the problem of lithium-ion battery being extracted during high-speed charging is solved, the cycle performance and life are improved, and the battery is stable and efficient charging and discharge is achieved.
Patent Information
- Application Number
- CN202411270545.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional magnification lithium-ion batteries are prone to lithium removal when charging at high rates, resulting in internal short circuits and thermal runaway, and have a short cycle life, making them difficult to use for a long time.
By controlling the particle size, coating surface density and compaction density of the positive and negative electrode active materials, the electrode structure is optimized, combined with appropriate conductive and binder ratios, the lithium ion diffusion resistance is reduced, the lithium-ion evolution phenomenon is reduced, and the battery is improved. Cyclic performance.
It effectively reduces the diffusion resistance of lithium ions, improves the diffusion speed of lithium ions, extends the stability of the electrode structure, improves the cycling performance and fast charging and release performance of the battery, and extends the service life of the battery.
Smart Images

Figure CN119208700A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery cell and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are secondary batteries (rechargeable batteries) that rely on the movement of lithium ions between the positive and negative electrodes to work. Compared with lead-acid batteries, nickel-metal hydride batteries, nickel-ion batteries, etc., lithium-ion batteries can provide higher energy density and longer cycle life. However, compared with fuel-powered batteries, lithium-ion batteries take a long time to fully charge. Therefore, charging to a state of charge of 80% (SOC) within 15 minutes is a goal of commercial lithium-ion batteries.
[0003] A rate-type lithium-ion battery is a lithium-ion battery that can be charged and discharged at a high rate under specific conditions. Traditional rate-type lithium-ion batteries can meet the requirements of high-rate discharge, but the battery is prone to lithium deposition when charged at a high rate, resulting in internal short circuits and thus thermal runaway of the battery.
[0004] In the related art, there are lithium-ion batteries that can meet the requirements of fast charging and discharging and prevent thermal runaway of the battery. However, the cycle life of the lithium-ion battery is short and it is difficult to use it for a long time. Summary of the invention
[0005] In view of the above problems, the present invention provides a battery cell and a preparation method thereof, and a lithium-ion battery, aiming to improve the problem of poor cycle performance of fast-charge and fast-discharge lithium-ion batteries.
[0006] In a first aspect, the present invention provides a battery cell, comprising: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating, wherein the positive electrode active coating comprises a positive electrode active material, and the particle size D of the positive electrode active material is 50 0.5 μm-5 μm; and / or,
[0007] The negative electrode sheet includes a negative electrode current collector and a negative electrode active coating, the negative electrode active coating includes a negative electrode active material, and the particle size D of the negative electrode active material is 50 3μm-10μm.
[0008] In one embodiment, the single-sided coating density of the positive electrode active coating is 7 mg / cm 2 -13mg / cm 2 ; and / or, the single-sided coating density of the negative electrode active coating is 4 mg / cm 2 -8mg / cm 2 .
[0009] In one embodiment, the compaction density of the positive electrode sheet is 2.3 g / cm 3-3.4g / cm 3 and / or,
[0010] The compaction density of the negative electrode is 1.0g / cm 3 -1.6g / cm 3 .
[0011] In one embodiment, the positive electrode active material is lithium nickel cobalt manganese oxide; and / or,
[0012] The negative electrode active material is selected from at least one of graphite, soft carbon and hard carbon.
[0013] In one embodiment, the positive electrode active coating further includes a positive electrode conductive agent, and the mass ratio of the positive electrode conductive agent to the positive electrode active material is (0.005-0.2):1; and / or, the negative electrode active coating further includes a negative electrode conductive agent, and the mass ratio of the negative electrode conductive agent to the negative electrode active material is (0.005-0.2):1.
[0014] In one embodiment, the positive electrode conductive agent and the negative electrode conductive agent are both selected from at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
[0015] In one embodiment, the positive electrode active coating further includes a positive electrode binder, and the mass ratio of the positive electrode binder to the positive electrode active material is (0.005-0.2):1; and / or, the negative electrode active coating further includes a negative electrode binder, and the mass ratio of the negative electrode binder to the negative electrode active material is (0.005-0.2):1.
[0016] In one embodiment, the positive electrode binder is polyvinylidene fluoride; and / or the negative electrode binder is selected from at least one of carboxymethyl cellulose and styrene-butadiene rubber.
[0017] In one embodiment, the separator is a polypropylene separator, and the porosity of the polypropylene separator is 45%-55%.
[0018] In one embodiment, the electrolyte includes an electrolyte, a solvent, and an additive;
[0019] The electrolyte is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, and lithium difluorobis(oxalatophosphate); and / or the solvent is selected from at least one of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate; and / or the additive is selected from at least one of vinylene carbonate, polystyrene, fluoroethylene carbonate, vinyl sulfate, and tris(trimethylsilyl)phosphate.
[0020] In a second aspect, the present invention provides a method for preparing a battery monomer, comprising:
[0021] The positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the positive electrode solvent are mixed to form a positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting;
[0022] The negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the negative electrode solvent are mixed to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting;
[0023] The positive electrode sheet, the negative electrode sheet and the separator are assembled into a battery cell component, and then packaged, injected, formed, vented, sealed and divided into different capacities to obtain a battery cell.
[0024] In a third aspect, the present invention further provides a lithium-ion battery, comprising at least one of the above-mentioned battery cells or a battery cell prepared by the above-mentioned preparation method.
[0025] The present invention controls the particle size D of the positive electrode active material 50 0.5 μm-5 μm and / or controlling the particle size D of the negative electrode active material 50 The thickness of the electrode is 3μm-10μm, which can reduce the concentration gradient between the electrode surface and the inside of the electrode, thereby reducing the diffusion resistance of lithium ions inside the battery, increasing the diffusion rate of lithium ions, and reducing the occurrence of lithium precipitation. On the one hand, the reduction of lithium precipitation reduces the volume change of the electrode, so that the electrode structure can remain relatively stable during the cycle process. On the other hand, the reduction of lithium precipitation can effectively utilize the active lithium, thereby improving the cycle performance of the battery. Therefore, the present invention can improve the problem of poor cycle performance of fast-charge and fast-discharge lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a rate cycle curve diagram of a battery cell in one embodiment of the present invention;
[0027] Figure 2 is a rate charging curve diagram of a battery cell in one embodiment of the present invention;
[0028] Figure 3 FIG. 4 is a rate discharge curve diagram of a battery cell in an embodiment of the present invention. DETAILED DESCRIPTION
[0029] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention and are therefore only used as examples and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0031] In the description of the embodiments of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0032] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0033] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0034] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two), and similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces). The term "at least one" refers to one or more.
[0035] A rate-type lithium-ion battery is a lithium-ion battery that can be charged and discharged at a high rate under specific conditions. Traditional rate-type lithium-ion batteries can meet high-rate discharge, but the battery is prone to lithium precipitation when charged at a high rate. On the one hand, it is because of the ion diffusion rate limitation. When charging at a high rate, the electrochemical reaction rate inside the battery is accelerated, and the diffusion rate of lithium ions in the positive and negative electrode materials is limited. If the charging speed is too fast, the lithium ions will not have time to embed into the negative electrode material, and will accumulate on the negative electrode surface to form lithium metal, that is, lithium precipitation; on the other hand, it is because of the serious polarization phenomenon. When charging at a high rate, the lithium ion concentration on the electrode surface changes rapidly, resulting in a large concentration gradient between the electrode surface and the inside of the electrode. This concentration polarization will increase the diffusion resistance of lithium ions in the electrode, further aggravating the accumulation of lithium ions on the negative electrode surface, thereby causing lithium precipitation; high-rate charging will also cause the battery's electrode potential to deviate from the equilibrium potential, increase electrochemical polarization, and excessively reduce the negative electrode potential, which may be lower than the deposition potential of lithium, thereby causing lithium metal to precipitate on the negative electrode surface. Therefore, when conventional rate-type lithium-ion batteries are charged at high rates, internal short circuits may occur due to lithium deposition, leading to thermal runaway of the battery.
[0036] Therefore, the fast charge and discharge performance of the battery can be improved by increasing the diffusion rate of lithium ions or reducing the polarization phenomenon. However, the lithium-ion batteries with fast charge and discharge performance in the related art still have the problem of short cycle life and difficulty in long-term use.
[0037] Based on the above considerations, the present invention provides a battery cell, including: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the positive electrode sheet includes a positive electrode current collector and a positive electrode active coating, the positive electrode active coating includes a positive electrode active material, and the particle size D of the positive electrode active material is 50 0.5 μm-5 μm; and / or, the negative electrode sheet includes a negative electrode current collector and a negative electrode active coating, the negative electrode active coating includes a negative electrode active material, and the particle size D of the negative electrode active material is 50 3μm-10μm.
[0038] The positive electrode active coating refers to the active material layer coated on the positive electrode current collector. The core component of the positive electrode active coating is the positive electrode active material. During the charging process, the positive electrode active material obtains electrons from the external circuit, and lithium ions are released from the electrolyte and embedded in the positive electrode active material; during the discharge process, lithium ions are released from the positive electrode active material, enter the negative electrode through the electrolyte, and electrons flow from the positive electrode to the negative electrode through the external circuit, thereby generating current. The positive electrode active material determines the key performance indicators of the battery, such as capacity and voltage.
[0039] The negative electrode active coating refers to the active material layer coated on the negative electrode current collector. The core component of the negative electrode active coating is the negative electrode active material. During the charging process, lithium ions are embedded into the negative electrode active material from the positive electrode through the electrolyte; during the discharging process, lithium ions are released from the negative electrode active material and return to the positive electrode through the electrolyte, thereby realizing the charging and discharging function of the battery.
[0040] Particle size D 50 The median particle size refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%, that is, the particles below and above this particle size each account for 50% of the total number of particles.
[0041] Particle size D of positive electrode active material 50 0.5 μm-5 μm refers to the particle size D of the positive electrode active material 50 It can be any value between 0.5 and 5. For example, the particle size D of the positive electrode active material 50 It can be 0.5μm, 1μm, 2μm, 3μm, 4μm, or 5μm.
[0042] Particle size D of negative electrode active material 50 3μm-10μm refers to the particle size D of the negative electrode active material 50 It can be any value between 3 and 10. For example, the particle size D of the positive electrode active material 50 It can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm.
[0043] Setting the particle size D of the positive electrode active material 50 0.5 μm-5 μm and / or the particle size D of the negative electrode active material 50 The particle size of the active material is 3μm-10μm. The small particle size of the active material can make the lithium ions more evenly distributed inside the material, thereby reducing the concentration gradient between the electrode surface and the inside of the electrode, thereby reducing the diffusion resistance of lithium ions inside the battery and increasing the diffusion rate of lithium ions. In addition, the small particle size can shorten the diffusion path of lithium ions in the active material and increase the diffusion coefficient of lithium ions. Therefore, setting the positive electrode active material and the negative electrode active material in the above particle size range can reduce the occurrence of lithium precipitation.
[0044] The reduction of lithium precipitation reduces the volume change of the electrode, so that the electrode structure can remain relatively stable during the cycle. On the other hand, the reduction of lithium precipitation can effectively utilize the active lithium. Therefore, the present invention can improve the problem of poor cycle performance of fast-charge and fast-discharge lithium-ion batteries.
[0045] According to some embodiments of the present invention, the single-sided coating density of the positive electrode active coating is 7 mg / cm 2 -13mg / cm 2; and / or, the single-sided coating density of the negative electrode active coating is 4 mg / cm 2 -8mg / cm 2 .
[0046] The single-sided coating density of the positive electrode active coating refers to the mass of the positive electrode active coating per unit area on one side of the positive electrode current collector. The single-sided coating density of the positive electrode active coating is 7 mg / cm 2 -13mg / cm 2 The single-sided coating area density of the positive electrode active coating can be any value between 7 and 13. For example, the single-sided coating area density of the positive electrode active coating can be 7 mg / cm 2 , 8mg / cm 2 、10mg / cm 2 、13mg / cm 2 .
[0047] The single-sided coating density of the negative electrode active coating refers to the mass of the negative electrode active coating per unit area on one side of the negative electrode current collector. The single-sided coating density of the negative electrode active coating is 4 mg / cm 2 -8mg / cm 2 It means that the single-sided coating area density of the negative electrode active coating can be any value between 4 and 8. For example, the single-sided coating area density of the negative electrode active coating can be 4 mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 8mg / cm 2 .
[0048] If the single-sided coating density of the active coating is too high, the utilization rate of the electrode active material will be reduced and ion diffusion will be difficult, thus affecting the rate performance and cycle performance of the battery; if the surface density is too low, the capacity of the battery will be reduced.
[0049] According to some embodiments of the present invention, the compaction density of the positive electrode sheet is 2.3 g / cm 3 -3.4g / cm 3 ; and / or, the compaction density of the negative electrode sheet is 1.0g / cm 3 -1.6g / cm 3 .
[0050] The compaction density refers to the mass per unit volume of the electrode. The compaction density of the positive electrode is 2.3g / cm 3 -3.4g / cm 3 It means that the compaction density of the positive electrode sheet can be any value between 2.3 and 3.4. For example, the compaction density of the positive electrode sheet can be 2.3 g / cm 3 , 2.6g / cm 3 、3.0g / cm3 、3.4g / cm 3 The compaction density of the negative electrode is 1.0g / cm 3 -1.6g / cm 3 It means that the compaction density of the negative electrode sheet can be any value between 1.0 and 1.6. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 , 1.3g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 .
[0051] The compaction density of the positive electrode is set to 2.3 g / cm 3 -3.4g / cm 3 , the compaction density of the negative electrode is 1.0g / cm 3 -1.6g / cm 3 The ion conduction and ion diffusion paths of the electrode can be optimized, thereby improving the rate performance of the battery. The compaction density in this range can ensure the stability of the electrode during the charge and discharge cycle, reduce the shedding of active materials and the deformation of the electrode, and thus extend the cycle life of the battery.
[0052] According to some embodiments of the present invention, the positive electrode active material is lithium nickel cobalt manganese oxide; and / or the negative electrode active material is selected from at least one of graphite, soft carbon and hard carbon.
[0053] Lithium Nickel Cobalt Manganese Oxide (LiNiCoMnO 2 , NCM) is a ternary cathode material, with types such as nickel cobalt manganese oxide 111, nickel cobalt manganese oxide 523, nickel cobalt manganese oxide 622 and nickel cobalt manganese oxide 811. Nickel cobalt manganese oxide has a high energy density, which helps to improve the battery's endurance. Nickel cobalt manganese oxide also has excellent cycle stability, which can keep the battery performing well after multiple charge and discharge cycles, helping to extend the battery's service life.
[0054] Graphite has a complete layered crystal structure, in which electrons can move relatively freely, and has good conductivity, which can ensure the rapid transmission of electrons during the battery charging and discharging process, reduce the internal resistance of the battery, and improve the battery charging and discharging efficiency. Soft carbon can still maintain good structural and performance stability after multiple charge and discharge cycles, and has a good cycle life. Hard carbon materials can withstand a large current density, and can quickly complete the embedding and extraction of lithium ions during the fast charging process, realizing the fast charging function.
[0055] According to some embodiments of the present invention, the positive electrode active coating also includes a positive electrode conductor, and the mass ratio of the positive electrode conductor to the positive electrode active material is (0.005-0.2):1; and / or, the negative electrode active coating also includes a negative electrode conductor, and the mass ratio of the negative electrode conductor to the negative electrode active material is (0.005-0.2):1.
[0056] The mass ratio of the positive electrode conductive agent to the positive electrode active material is (0.005-0.2):1, which means that the mass of the positive electrode conductive agent is 0.5%-20% of the mass of the positive electrode active material. For example, the mass ratio of the positive electrode conductive agent to the positive electrode active material can be 0.005:1, 0.01:1, 0.02:1, 0.05:1, 0.1:1, 0.2:1. The negative electrode conductive agent is set in the same way.
[0057] The positive electrode conductive agent with a ratio in this range can form a good conductive network between the positive electrode material particles, promote rapid electron transmission, reduce the internal resistance of the battery, help achieve a more uniform current distribution during the charge and discharge process, reduce local polarization, and thus improve the battery's cycle performance. The negative electrode conductive agent with a ratio in this range can improve the negative electrode's electron transmission capacity, promote the embedding and extraction process of lithium ions in the negative electrode, and thus improve the battery's rate performance and cycle performance.
[0058] According to some embodiments of the present invention, the positive electrode conductive agent and the negative electrode conductive agent are both selected from at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
[0059] The carbon fiber can be vapor grown carbon fiber (VGCF), which has excellent electrical conductivity and can improve the charge and discharge efficiency and rate performance of the battery.
[0060] According to some embodiments of the present invention, the positive electrode active coating further includes a positive electrode binder, and the mass ratio of the positive electrode binder to the positive electrode active material is (0.005-0.2):1; and / or, the negative electrode active coating further includes a negative electrode binder, and the mass ratio of the negative electrode binder to the negative electrode active material is (0.005-0.2):1.
[0061] The binder ratio within this range can ensure good bonding strength between the active material, conductive agent and current collector, and maintain the integrity of the electrode structure. During the long-term charge and discharge process of the battery, the active material is not easy to fall off, so that the battery has better cycle performance and service life.
[0062] According to some embodiments of the present invention, the positive electrode binder is polyvinylidene fluoride; and / or the negative electrode binder is selected from at least one of carboxymethyl cellulose and styrene-butadiene rubber.
[0063] Polyvinylidene fluoride has strong bonding ability, high chemical stability and good electrochemical stability. It can maintain good bonding effect in various environments, thus ensuring the stability of the electrode structure and improving the cycle performance and service life of the battery. Carboxymethyl cellulose and styrene-butadiene rubber as negative electrode binders also have strong bonding force and good electrochemical stability.
[0064] According to some embodiments of the present invention, the membrane is a polypropylene membrane, and the porosity of the polypropylene membrane is 45%-55%.
[0065] The use of high-porosity polypropylene diaphragms can provide more space for electrolyte storage and lithium ion transmission, which allows lithium ions to migrate more smoothly between the positive and negative electrodes during the battery charging and discharging process, reducing the diffusion resistance of lithium ions, allowing the battery to charge and discharge faster, thereby showing better rate performance. In addition, high-porosity diaphragms can provide a certain buffer space, reduce damage to the diaphragm structure, and reduce the growth rate of the interface resistance between the electrode material and the diaphragm, thereby extending the cycle life of the battery.
[0066] According to some embodiments of the present invention, the electrolyte includes an electrolyte, a solvent, and an additive;
[0067] The electrolyte is selected from lithium hexafluorophosphate (LiPF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiODFB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalate)phosphate (LiODFP); and / or the solvent is selected from at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC); and / or the additive is selected from at least one of vinylene carbonate (VC), polystyrene (PS), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), and tris(trimethylsilyl) phosphate (TMSP).
[0068] As a film-forming additive, vinylene carbonate can make solvent molecules preferentially form a dense SEI film (solid electrolyte interface film) on the surface of the negative electrode, thereby increasing the energy density and service life of lithium-ion batteries. Polystyrene additives help improve the structural stability of the electrode or participate in the formation of a specific interface film. Fluorinated vinyl carbonate additives can generate LiF-rich SEI films with excellent low-temperature performance, which can improve the safety performance of the battery. Vinyl sulfate additives can reduce the resistance of the battery and can also form an SEI film on the surface of the electrode, thereby effectively improving the interface structure between the electrode and the electrolyte, thereby improving battery performance. Tris(trimethylsilyl)phosphate additives can significantly improve the room temperature and high temperature cycle performance of lithium-ion batteries.
[0069] According to some embodiments of the present invention, the present invention provides a method for preparing a battery monomer, comprising:
[0070] The positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the positive electrode solvent are mixed to form a positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting;
[0071] The negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the negative electrode solvent are mixed to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting;
[0072] The positive electrode sheet, the negative electrode sheet and the separator are assembled into a battery cell component, and then packaged, injected, formed, vented, sealed and divided into different capacities to obtain a battery cell.
[0073] Packaging refers to the process of sealing the battery cell assembly and related components into an aluminum shell or a steel shell, or sealing the battery cell assembly and related components in a soft pack. Injection is the process of injecting electrolyte into the assembled battery cell. Formation is a series of operations and treatments on the first charged battery to form a stable solid electrolyte interface film (SEI film) on the electrode surface and activate the electrochemical properties of the battery. Exhaust and secondary sealing refers to the process of discharging the gas generated inside the battery during the formation process and resealing the battery. Capacity sorting is the process of capacity sorting of batteries. By performing charge and discharge tests on the battery, the actual capacity of the battery is determined, and the battery is classified according to capacity.
[0074] In some embodiments, the solid content of the positive electrode slurry may be 55%-75%, and the solid content of the negative electrode slurry may be 45%-55%.
[0075] According to some embodiments of the present invention, the present invention further provides a lithium-ion battery, comprising at least one of the above-mentioned battery cells or a battery cell prepared by the above-mentioned preparation method. The specific configuration of the battery cell refers to the above-mentioned embodiments. Since the lithium-ion battery of the present invention adopts all the technical solutions of all the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0076] The following is an explanation through specific embodiments.
[0077] Example 1
[0078] A battery cell has a designed capacity of 5Ah and comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0079] The positive electrode sheet includes a positive electrode current collector and a positive electrode active coating coated on the surface of the positive electrode current collector. The positive electrode current collector is aluminum foil; the positive electrode active coating includes the following components by mass percentage: 97% lithium nickel cobalt manganese oxide, 1% conductive carbon black, 1% carbon nanotubes, and 1% polyvinylidene fluoride, wherein the particle size D of the lithium nickel cobalt manganese oxide is 50 The single-sided coating density of the positive electrode active coating is 10 mg / cm 2 The compaction density of the positive electrode is 3g / cm 3 .
[0080] The negative electrode sheet includes a negative electrode current collector and a negative electrode active coating coated on the surface of the negative electrode current collector. The negative electrode current collector is copper foil; the negative electrode active coating includes the following components by mass percentage: 32% graphite, 32% soft carbon, 30% hard carbon, 2% conductive carbon black, 2% VGCF, 1% carboxymethyl cellulose, and 1% styrene-butadiene rubber, wherein the particle size D of the mixture of graphite, soft carbon and hard carbon is 50 The single-sided coating density of the negative electrode active coating is 6 mg / cm 2 The compaction density of the negative electrode is 1.3g / cm 3 .
[0081] The diaphragm is a polypropylene diaphragm with a porosity of 50%.
[0082] The electrolyte includes electrolyte, solvent and additive. The electrolyte is LiPF 6 、LiFSI、LiODFB、LiPO 2 F 2 and LiODFP in a mass ratio of 24:3:1:1:1; the solvent is a mixture of EC, EMC, and DEC in a mass ratio of 1:4:1.67; the additive is a mixture of VC, PS, FEC, DTD, and TMSP in a mass ratio of 1:1:1:1:1.
[0083] The method for preparing a battery cell comprises:
[0084] Preparation of positive electrode sheet: Lithium nickel cobalt manganese oxide, conductive carbon black, carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone (NMP) are mixed to form positive electrode slurry, and the solid content of the positive electrode material is 60%. The positive electrode slurry is evenly coated on aluminum foil, and the positive electrode sheet is obtained after drying, rolling and cutting.
[0085] Preparation of negative electrode sheet: Graphite, soft carbon, hard carbon, conductive carbon black, VGCF, carboxymethyl cellulose, styrene-butadiene rubber and deionized water are mixed to form negative electrode slurry, and the solid content of the negative electrode slurry is 50%. The negative electrode slurry is evenly coated on the copper foil, and the negative electrode sheet is obtained after drying, rolling and cutting.
[0086] The positive electrode sheet, negative electrode sheet and separator are made into a battery cell by Z-shaped stacking, with the positive and negative electrode tabs located on the same side of the battery cell, and the outermost circle of the stack adopts a structure that ends with negative electrode sheets on the upper and lower sides of the stack. Then, the battery cell is obtained through welding, packaging, liquid injection, formation, exhaust, secondary sealing and capacity division.
[0087] Example 2
[0088] Different from Example 1, the particle size D of the lithium nickel cobalt manganese oxide in this embodiment is 50 The thickness is 5 μm, and the rest is the same as in Example 1.
[0089] Example 3
[0090] Different from Example 1, the particle size D of the lithium nickel cobalt manganese oxide in this embodiment is 50 is 0.5 μm, and the rest is the same as in Example 1.
[0091] Example 4
[0092] Different from Example 1, the particle size D of the mixture of graphite, soft carbon and hard carbon in this example is 50 The thickness is 8 μm, and the rest is the same as in Example 1.
[0093] Example 5
[0094] Different from Example 1, the particle size D of the mixture of graphite, soft carbon and hard carbon in this example is 50 The thickness is 10 μm, and the rest is the same as in Example 1.
[0095] Example 6
[0096] Different from Example 1, the particle size D of the lithium nickel cobalt manganese oxide in this embodiment is 50 The particle size D of the mixture of graphite, soft carbon and hard carbon is 3 μm. 50 The thickness is 4 μm, and the rest is the same as in Example 1.
[0097] Example 7
[0098] Different from Example 1, the negative electrode active coating in this example includes the following components in percentage by mass: 62% graphite, 16% soft carbon, 16% hard carbon, 2% conductive carbon black, 2% VGCF, 1% carboxymethyl cellulose, and 1% styrene-butadiene rubber. The rest is the same as Example 1.
[0099] Example 8
[0100] Different from Example 1, the single-sided coating density of the positive electrode active coating in this example is 13 mg / cm 2 The compaction density of the positive electrode is 3.4g / cm 3 , the rest is the same as Example 1.
[0101] Example 9
[0102] Different from Example 1, the single-sided coating density of the negative electrode active coating in this example is 4 mg / cm 2 The compaction density of the negative electrode is 1g / cm 3 , the rest is the same as Example 1.
[0103] Comparative Example 1
[0104] Different from Example 1, the particle size D of the lithium nickel cobalt manganese oxide in this embodiment is 50 The thickness is 7 μm, and the rest is the same as in Example 1.
[0105] Comparative Example 2
[0106] Different from Example 1, the particle size D of the mixture of graphite, soft carbon and hard carbon in this example is 50 is 15 μm, and the rest is the same as Example 1.
[0107] Comparative Example 3
[0108] Different from Example 1, the single-sided coating density of the positive electrode active coating in this example is 15 mg / cm 2 The compaction density of the positive electrode is 4g / cm 3 , the rest is the same as Example 1.
[0109] Comparative Example 4
[0110] Different from Example 1, the single-sided coating density of the negative electrode active coating in this example is 10 mg / cm 2 The compaction density of the negative electrode is 2g / cm 3 , the rest is the same as Example 1.
[0111] Performance Testing
[0112] The battery cells in Examples 1-9 and Comparative Examples 1-4 were subjected to rate charge, rate discharge and 10C / 10C cycle (100% DOD) tests.
[0113] Rate charging test method:
[0114] 1. At normal temperature and pressure, discharge the battery cell at a constant current of 1C to 2.75V and let it stand for 10 minutes;
[0115] 2. Charge at 1C constant current until 4.2V, then switch to constant voltage charging. Stop charging when the charging current drops to 0.05C and let it stand for 10 minutes.
[0116] 3. Discharge at 1C constant current to 2.75V and let stand for 10 minutes;
[0117] 4. Repeat steps 2-3 once, and take the second discharge capacity as the actual capacity of the battery;
[0118] 5. After fully charging at the required rate current (10C, 20C, 30C, 40C) with constant current and constant voltage, stop charging and let it stand for 10 minutes;
[0119] 6. Discharge at 1C constant current to 2.75V and let stand for 10 minutes;
[0120] Rate discharge test method:
[0121] 1. At normal temperature and pressure, discharge the battery cell at a constant current of 1C to 2.75V and let it stand for 10 minutes;
[0122] 2. Charge at 1C constant current until 4.2V, then switch to constant voltage charging. Stop charging when the charging current drops to 0.05C and let it stand for 10 minutes.
[0123] 3. Discharge at 1C constant current to 2.75V and let stand for 10 minutes;
[0124] 4. Repeat steps 2-3 once, and take the second discharge capacity as the actual capacity of the battery;
[0125] 5. Charge at 1C constant current until 4.2V, then switch to constant voltage charging. Stop charging when the charging current drops to 0.05C and let it stand for 10 minutes.
[0126] 6. Discharge at the required rate current (10C, 20C, 30C, 40C) to 2.75V and let stand for 10 minutes;
[0127] Cycle test method:
[0128] 1. At normal temperature and pressure, discharge the battery cell at a constant current of 1C to 2.75V and let it stand for 10 minutes;
[0129] 2. Charge at 1C constant current until 4.2V, then switch to constant voltage charging. Stop charging when the charging current drops to 0.05C and let it stand for 10 minutes.
[0130] 3. Discharge at 1C constant current to 2.75V and let stand for 10 minutes;
[0131] 4. Repeat steps 2-3 once, and take the second discharge capacity as the actual capacity of the battery;
[0132] 5. Charge at 10C constant current until 4.2V, then switch to constant voltage charging. Stop charging when the charging current drops to 0.05C and let it stand for 10 minutes.
[0133] 6. Discharge at 10C constant current to 2.75V and let stand for 10 minutes;
[0134] 7. Repeat steps 5-6 for testing.
[0135] Test Results
[0136] The cycle performance of the battery cell is shown in Table 1, the charge and discharge performance of the battery cell is shown in Table 2, and the rate cycle curve of the battery cell in Example 1 is shown in Table 2. Figure 1 As shown, the rate charging curve is as follows Figure 2 As shown, the rate discharge curve is as follows Figure 3 shown.
[0137] Table 1 Rate cycle performance of battery cells in Examples 1-9 and Comparative Examples 1-4
[0138]
[0139]
[0140] It can be seen from Table 1 that the capacity retention rate of the battery monomer of the embodiment of the present invention is still greater than 70% after 5000 cycles at 10C / 10C (100% DOD), while the capacity retention rate of the battery monomers in Comparative Examples 1 and 2 has been reduced to about 30% after 3000 cycles at 10C / 10C (100% DOD), and the capacity retention rate of the battery monomers in Comparative Examples 3 and 4 has been as low as 50.91% and 36.76% after 500 cycles at 10C / 10C (100% DOD), indicating that the battery monomers of the embodiment of the present invention have a higher cycle life.
[0141] It can be seen from the comparison of Examples 1-6 and Comparative Examples 1-2 that the present invention can significantly improve the cycle performance of the battery by optimizing the particle size of the positive electrode active material and the negative electrode active material. This is because the active material with a small particle size can reduce the concentration gradient between the electrode surface and the inside of the electrode, thereby reducing the diffusion resistance of lithium ions inside the battery, increasing the diffusion rate of lithium ions, and reducing the occurrence of lithium precipitation. The reduction of lithium precipitation reduces the volume change of the electrode, so that the electrode structure can remain relatively stable during the cycle. On the other hand, the reduction of lithium precipitation can effectively utilize the active lithium. Thereby improving the cycle performance of the battery.
[0142] By comparing Examples 8 and 9 with Comparative Examples 3 and 4, it can be seen that the present invention can also improve the cycle performance of the battery by optimizing the surface density and compaction density of the positive and negative electrodes. The surface density and compaction density in the embodiments of the present invention can improve the utilization rate of the active material, ensure the stability of the pole piece during the charge and discharge cycle, reduce the shedding of the active material and the deformation of the pole piece, thereby extending the cycle life of the battery.
[0143] Table 2 Rate charge and discharge performance of battery cells in Examples 1-9 and Comparative Examples 1-4
[0144]
[0145]
[0146] It can be seen from Table 1 that the 40C charging constant current ratio of the battery cell in the embodiment of the present invention is ≥50%, and the 40C discharge retention rate is ≥90%, while the 40C charging constant current ratio of the battery cell in Comparative Example 1 is 48%, and the 40C discharge retention rate is only 47%, and the 40C charging constant current ratio of the battery cell in Comparative Example 2 is only 7%, and the 40C discharge retention rate is only 35%.
[0147] By comparing Examples 1-6 and Comparative Examples 1-2, it can be seen that the present invention can significantly improve the fast charge and discharge performance of the battery by optimizing the particle sizes of the positive electrode active material and the negative electrode active material. This is because the small particle size of the active material increases the diffusion rate of lithium ions, and the small particle size of the active material has a larger specific surface area and can provide more reactive sites, thereby improving the charging rate.
[0148] By comparing Examples 8 and 9 with Comparative Examples 3 and 4, it can be seen that the present invention can also improve the fast charge and discharge performance of the battery by optimizing the surface density and compaction density of the positive and negative electrodes.
[0149] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A battery cell, comprising: A positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating, the positive electrode active coating comprises a positive electrode active material, and the particle size D of the positive electrode active material is 50 0.5 μm-5 μm; and / or, The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating, wherein the negative electrode active coating comprises a negative electrode active material, and the particle size D of the negative electrode active material is 50 3μm-10μm.
2. The battery cell according to claim 1, characterized in that: The single-sided coating density of the positive electrode active coating is 7 mg / cm 2 -13mg / cm 2 and / or, The single-sided coating density of the negative electrode active coating is 4 mg / cm 2 -8mg / cm 2 .
3. The battery cell according to claim 1, characterized in that: The compaction density of the positive electrode sheet is 2.3 g / cm 3 -3.4g / cm 3 and / or, The compaction density of the negative electrode plate is 1.0 g / cm 3 -1.6g / cm 3 .
4. The battery cell according to any one of claims 1 to 3, characterized in that: The positive electrode active material is lithium nickel cobalt manganese oxide; and / or, The negative electrode active material is selected from at least one of graphite, soft carbon and hard carbon.
5. The battery cell according to any one of claims 1 to 3, characterized in that: The positive electrode active coating further comprises a positive electrode conductive agent, wherein the mass ratio of the positive electrode conductive agent to the positive electrode active material is (0.005-0.2):1; and / or, The negative electrode active coating also includes a negative electrode conductive agent, and the mass ratio of the negative electrode conductive agent to the negative electrode active material is (0.005-0.2):
1.
6. The battery cell according to claim 5, characterized in that: The positive electrode conductive agent and the negative electrode conductive agent are both selected from at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
7. The battery cell according to any one of claims 1 to 3, characterized in that: The positive electrode active coating further comprises a positive electrode binder, wherein the mass ratio of the positive electrode binder to the positive electrode active material is (0.005-0.2):1; and / or, The negative electrode active coating also includes a negative electrode binder, and the mass ratio of the negative electrode binder to the negative electrode active material is (0.005-0.2):
1.
8. The battery cell according to claim 7, characterized in that: The positive electrode binder is polyvinylidene fluoride; and / or the negative electrode binder is selected from at least one of carboxymethyl cellulose and styrene-butadiene rubber.
9. The battery cell according to claim 1, characterized in that: The diaphragm is a polypropylene diaphragm, and the porosity of the polypropylene diaphragm is 45%-55%.
10. The battery cell according to claim 1, characterized in that: The electrolyte comprises an electrolyte, a solvent and an additive; The electrolyte is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, and lithium difluorobis(oxalatophosphate); and / or The solvent is selected from at least one of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate; and / or, The additive is selected from at least one of vinylene carbonate, polystyrene, fluoroethylene carbonate, vinyl sulfate, and tris(trimethylsilyl)phosphate.
11. A method for preparing a battery monomer according to any one of claims 1 to 10, characterized in that: include: The positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the positive electrode solvent are mixed to form a positive electrode slurry, the positive electrode slurry is coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and cutting; The negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the negative electrode solvent are mixed to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and the negative electrode sheet is obtained after drying, rolling and cutting; The positive electrode sheet, the negative electrode sheet and the separator are assembled into a battery core assembly, and then packaged, injected, formed, exhausted, sealed and divided into different capacities to obtain a battery cell.
12. A lithium ion battery, characterized in that: The invention comprises at least one battery cell according to any one of claims 1 to 10 or a battery cell prepared by the preparation method according to claim 11.
Citation Information
Cited By
Lithium ion battery and preparation method thereof
CN119786703A
Battery monomer, battery device and electric equipment
CN120545616A
Negative electrode sheet and preparation method therefor, battery, battery pack, and electric device
WO2026158101A1
Secondary battery, manufacturing method therefor, and electrical device
WO2026184250A1
Battery cell and preparation method therefor, and electric device
WO2026184252A1
